2018
DOI: 10.1093/cid/cix1140
|View full text |Cite
|
Sign up to set email alerts
|

The Continuing Burden of Advanced HIV Disease Over 10 Years of Increasing Antiretroviral Therapy Coverage in South Africa

Abstract: BackgroundAntiretroviral treatment (ART) has been massively scaled up to decrease human immunodeficiency virus (HIV)–related morbidity, mortality, and HIV transmission. However, despite documented increases in ART coverage, morbidity and mortality have remained substantial. This study describes trends in the numbers and characteristics of patients with very advanced HIV disease in the Western Cape, South Africa.MethodsAnnual cross-sectional snapshots of CD4 distributions were described over 10 years, derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 16 publications
(18 reference statements)
6
111
4
Order By: Relevance
“…Interestingly, many patients entering, or re-entering care, are treatment experienced [20,21]. In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20). The prevalence of advanced HIV disease was lower in the current study than reported in the literature [18][19][20][21]; however, this could have been due to the variable uses of CD4 testing across included countries within the current study.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, many patients entering, or re-entering care, are treatment experienced [20,21]. In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20). The prevalence of advanced HIV disease was lower in the current study than reported in the literature [18][19][20][21]; however, this could have been due to the variable uses of CD4 testing across included countries within the current study.…”
Section: Resultscontrasting
confidence: 63%
“…Further, reviewing CD4 data in nearly one million patients attending health care facilities within the IeDEA and COHERE cohorts across 55 countries found that not only has the proportion of patients entering care remained high across settings (31% in low-income countries, 40% in low-and middle-income countries, 29% in high-income countries), but these rates have plateaued over the past few years [19]. Interestingly, many patients entering, or re-entering care, are treatment experienced [20,21]. In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20).…”
Section: Resultsmentioning
confidence: 99%
“…The high frequency of missing data may be a function of less frequent CD4 monitoring as this is no longer needed to determine treatment eligibility, despite the continued recommendation of baseline CD4 measurement in national guidelines [19]. Similar findings were observed in South Africa under changes in CD4 monitoring policy [32] and may be expected in other settings as Treat All implementation continues [33], potentially limiting opportunities to evaluate the impact of this policy. Among patients enrolling in care after Treat All, we also observed negligible differences among patients grouped by baseline CD4 count with respect to six-month retention in care.…”
Section: Discussionmentioning
confidence: 75%
“…However, in spite of increasing ART coverage, HIV-related mortality and morbidity remained substantial. 36 The present-day need is to find the therapies against HIV that completely eradicate the virus but the viral clearance poses a challenge because of the proviral DNA integration into the cellular genome. 37 The first study stating the relation between HIV-1 and TRIM proteins employed the use of recombinant HIV-1 expressing green fluorescent protein and TRIM5α from Old world monkeys in human HeLa cells.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Current treatment against HIV includes combined Antiretroviral Treatment that have been found to control the HIV infection. However, in spite of increasing ART coverage, HIV‐related mortality and morbidity remained substantial . The present‐day need is to find the therapies against HIV that completely eradicate the virus but the viral clearance poses a challenge because of the proviral DNA integration into the cellular genome …”
Section: Introductionmentioning
confidence: 99%